Hubungan Asupan Protein dengan Kejadian Anemia pada Ibu Hamil di Posyandu Bakau Serip dan Sakura Indah Puskesmas Sambau Kota Batam - Nur Pita Apriyanti; Siska Pratiwi; Citra Dewi Anggraini (Lembaga Pengembangan Kinerja Dosen, 2025)
The study highlighted an alarming rise in anemia cases among pregnant women in Batam City, with a dramatic increase in incidence from 26.3% in 2022 to 52.65% in 2023. Conducted at Posyandu Bakau Serip and Sakura Indah Sambau Community Health Center, this cross-sectional research aimed to assess the correlation between protein intake and anemia incidence among 45 pregnant women selected using purposive sampling. Protein intake was evaluated through a Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ), and anemia was determined by measuring hemoglobin levels. Using the Chi-square test, the study revealed a significant relationship between protein intake and anemia (p = 0.031). Insufficient protein intake was associated with a notably higher risk of anemia. These findings emphasize the critical role of adequate protein consumption during pregnancy in reducing the risk of anemia and its associated complications.